2014
DOI: 10.1007/s11239-014-1050-0
|View full text |Cite
|
Sign up to set email alerts
|

Risk of venous thromboembolism among hospitalizations of adults with selected autoimmune diseases

Abstract: Previous research has suggested autoimmune diseases are risk factors for developing venous thromboembolism (VTE). We assessed whether having diagnoses of selected autoimmune diseases associated with anti-phospholipid antibodies—autoimmune hemolytic anemia (AIHA), immune thrombocytopenic purpura (ITP), rheumatoid arthritis (RA), and systemic lupus erythematosus (SLE)—were associated with having a VTE diagnosis among US adult hospitalizations. A cross-sectional study was conducted using the 2010 Nationwide Inpat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 30 publications
(38 reference statements)
1
32
0
Order By: Relevance
“…Patients with rheumatic diseases have more than double the risk of VTE compared to the general population, particularly when their disease is active [77][78][79][80][81]. This is not surprising given the association between inflammation and thrombosis [82].…”
Section: Venous Thromboembolismmentioning
confidence: 99%
“…Patients with rheumatic diseases have more than double the risk of VTE compared to the general population, particularly when their disease is active [77][78][79][80][81]. This is not surprising given the association between inflammation and thrombosis [82].…”
Section: Venous Thromboembolismmentioning
confidence: 99%
“…The adjusted odds ratio for recorded diagnoses of VTE with hospitalization for the diagnosis of SLE was 1.23 (95% CI; 1.15-1.32) and for RA was 1.17 (95% CI; 1.13-1.21). 6 A summary of the above studies is shown in Table 1. The data consistently show an increased risk of VTE associated with autoimmune diseases, especially related to hospitalization.…”
Section: Epidemiology Of Vte In Systemic Autoimmune Diseasesmentioning
confidence: 99%
“…Our aim was to add to the growing evidence of the association between autoimmune diseases and VTE and epidemiologic understanding in this regard [8–16]. We previously reported findings of a cross-sectional study using U.S. hospitalization data that indicated an increased likelihood of VTE diagnosis associated with a diagnosis of these autoimmune diseases [20]. The objectives of this study were to assess the risk of VTE among commercial health insurance enrollees who had a diagnosis of one or more of the same four autoimmune diseases using a longitudinal approach.…”
Section: Introductionmentioning
confidence: 99%